UTILIZATION OF AUGMENTED REALITY MEDIA TO ENHANCE DIGITAL LITERACY SKILLS IN SOCIAL STUDIES LEARNING - Tetep, Tetep; Dahlena, Alni (International Conference On Social Science Education, 2024)
Social studies education is textual learning, and is based on textbooks only, thus providing a lack of digital-based literacy in social studies learning. Where social studies learning must be aware of technological developments and learning media, as an effort to provide interest in learning for students. The tendency so far used by teachers is that social studies learning is only focused on textbooks, without providing innovative learning media that can integrate digitally. Social studies learning will provide literacy skills which are a challenge in the 21st century era, especially in realizing digital literacy skills, one of which is using augmented reality media. The aim of this research is to analyze the improvement of digital literacy skills with augmented reality media in social studies learning for students. The research method used is quantitative through a quasi-experimental research design by applying pretest and posttest instruments carried out by junior high school students. Next, the data was analyzed using SPSS IBM 26 analysis software. The results of this research can be identified that the application of augmented reality media has an impact on increasing students' digital literacy in social studies learning with the level of difference between the control class and the experimental class being quite significant. Through the implementation of augmented reality media, it can increase students' interest in literacy in social studies learning. Therefore, the implementation of augmented reality media can improve students' digital literacy skills in social studies learning quite significantly